Prediabetes Associates with Matrix Metalloproteinase-8 Activation and Contributes to the Rapid Destruction of Periodontal Tissues - Umeizudike, Kehinde Adesola; Aji, Nur Rahman Ahmad Seno; Niskanen, Katariina; Rantala, Iina; Sakellari, Dimitra; Grigoriadis, Andreas; Pätilä, Tommi; Gupta, Shipra; Sorsa, Timo; Räisänen, Ismo T. (European Journal of Dentistry, 2024)
Objective The aim of this cross-sectional study was to investigate the relationship between periodontitis, potential periodontitis oral fluid biomarkers, and prediabetes.Materials and Methods This study included 150 Greek adults aged 25 to 78 years who were tested with an Hemoglobin A1C (HBA1c) diagnostic system, an active-matrix metalloproteinase-8 (aMMP-8) point-of-care (PoC) test, and several salivary biomarkers enzyme-linked immunosorbent assay tests and gelatin zymography. A full-mouth clinical examination was performed to assess their periodontal and oral health status.Statistical Analysis The Kruskal–Wallis test was used to determine the statistically significant difference in the levels of periodontal oral fluid biomarkers between the different periodontitis stages, periodontitis grades, and the stages and grades of periodontitis combined. Spearman's rank correlation was performed to assess the strength and direction of the association between aMMP-8 and HbA1c levels (<5.7 and ≥5.7%) and with the other oral fluid biomarkers among patients with severe periodontitis. A two-sided p-value below 0.05 was considered statistically significant in this study.Results aMMP-8, but not total MMP-8 or other biomarkers, associated significantly with the stage and grade of periodontitis combined (p < 0.001, Kruskal–Wallis test). Among stage III grade C periodontitis patients, aMMP-8 levels were significantly positively correlated with prediabetes (Spearman's rho = 0.646, p = 0.044), total MMP-8 (rho = 0.636, p = 0.048), PMN Elastase (rho = 0.729, p = 0.017), total MMP-9 (rho = 0.721, p = 0.019), and total MMP-8/TIMP-1 molar ratio (rho = 0.879, p < 0.001).Conclusion Prediabetic disease development can upregulate MMP-8 expression (total MMP-8) in rapidly progressing, severe periodontitis, where MMP-8 latent species are further activated into their active forms (aMMP-8). Simultaneously, several proinflammatory biomarker levels are elevated in this tissue-destructive biomarker cascade. This development is easily detectable online/in real-time within 5 minutes by aMMP-8 PoC testing at the dentist's office.
Keywords: periodontitis; diagnosis; matrix metalloproteinase 8; biomarkers; point-of-care testing; prediabetes; diabetes